Equilibrium exchange rates in Southeastern Europe, Russia, Ukraine and Turkey : healthy or (Dutch) diseased? - Égert, Balázs; Suomen Pankki. Siirtymätalouksien tutkimuslaitos (BOFIT discussion papers, ISSN 1456-4564, 2005)
Tiivistelmä.
Keywords: valuuttakurssit; valutakurser; Exchange rates; Itä-Eurooppa; Ukraina; Turkki; Bulgaria; Romania; Venäjä; Kroatia; Croatia; Russia; Ukraine; Turkey